Theoretical dialogues between schools of critical thought: brief reflections on the Brazilian cultural formation (TEL Tempo, Espaço e Linguagem, 2022)
This article aims to establish a dialogue between schools of social thought that viewed formation as a possibility of emancipation/liberation of the subjects. A brief reflection about the Brazilian cultural formation reveals the need to read concepts produced with the desire for liberation/emancipation in a critical and adapted way according to local social configurations